The impact of steel protection in industrialized countries on Brazil's export capacity - Torsten Amelung (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1988)
Since the beginning of the 1970s most industrialized countries have been facing serious structural adjustment problems in the steel sector, which can be attributed mainly to two reasons. On the one hand, declining demand in industrialized countries caused overcapacities in their domestic production, while, on the other hand, NICs began to catch up in heavy industries, thus steadily penetrating the world steel market, which increasingly became a buyers' market . The immediate response of the industrialized nations was a new wave of protectionism and subsidization, as in all instances questions of national interests and politics were involved. However, in the case of the steel crisis these measures were not only applied with respect to declining industries, as they persist in industrialized countries. Following the infant industry argument, governments in NICs rendered considerable support to their steel industries.
Keywords: 330